2009
DOI: 10.1007/s00534-009-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of mucin expression in pancreatobiliary neoplasms

Abstract: Mucins are high molecular weight glycoproteins that play important roles in carcinogenesis and tumor invasion. We have described, for the first time, that pancreatic ductal adenocarcinomas (PDACs) with an aggressive behavior and a poor outcome expressed MUC1 (pan-epithelial membrane-associated mucin) but did not express MUC2 (intestinal-type secreted mucin), whereas intraductal papillary mucinous neoplasms (IPMNs) with indolent behavior and a favorable outcome did not express MUC1 but did express MUC2. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 74 publications
5
86
2
3
Order By: Relevance
“…20 Although molecular analyses of either of the two biliary precursor lesions are limited, the available information suggests underlying differences in terms of genetic alterations, as well as clinical distinctions in the invasive carcinomas arising in the respective contexts. [21][22][23] Emerging evidence suggests a number of similarities between IPMNs and IPNBs. For example, Zen et al analysed both entities with respect to clinicopathologic features, expression of lineageassociated proteins and prognostic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although molecular analyses of either of the two biliary precursor lesions are limited, the available information suggests underlying differences in terms of genetic alterations, as well as clinical distinctions in the invasive carcinomas arising in the respective contexts. [21][22][23] Emerging evidence suggests a number of similarities between IPMNs and IPNBs. For example, Zen et al analysed both entities with respect to clinicopathologic features, expression of lineageassociated proteins and prognostic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Mucins are also expressed in pancreatico-biliary neoplasm included biliary tract cancer. Furthermore, MUC expression pattern might reflect the cell differentiation type of biliary tract cancer like pancreatic intraductal papillary mucinus neoplasms, for example, gastric type presents a MUC1-/MUC2-/MUC5AC+/MUC6-profile, intestinal type presents a MUC1-/MUC2+/MUC5AC+/MUC6-profile, and pancreaticobiliary type presents a MUC1+/MUC2-/MUC5AC+/MUC6+ profile (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…MUC6 was positive in 31.3% of dysplasias, and 18.2% in CC. Several authors demonstrated higher expression of these mucins in both CC and dysplastic epithelium, emphasizing that they are important in characterizing biliary and pancreatic pre-neoplastic lesions (7,11,15,20,21,24) . Although these results apparently substantiate the usefulness of mucins 5 and 6 in the characterization of preneoplastic lesions, we observed that both were also expressed in reactive epithelium in 40.3% and 11.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although these results apparently substantiate the usefulness of mucins 5 and 6 in the characterization of preneoplastic lesions, we observed that both were also expressed in reactive epithelium in 40.3% and 11.9%, respectively. Up to now, studies describing the expression of gastric mucins in reactive biliary epithelium were not found in the literature (15,23,21) . Thus, gastric mucin expression in the reactional epithelium of intrahepatic bile ducts, associated with the lack of statistical significance of dysplasia expression, points to a limited role of these mucins in distinguishing reactive and pre-neoplastic lesions.…”
Section: Discussionmentioning
confidence: 99%